REDESAIN FURNITUR OPACSTATION PERPUSTAKAAN UNIVERSITAS SURABAYA SEBAGAI UPAYA PENINGKATAN ESTETIKA DAN EFEKTIVITAS FUNGSI FASILITAS DALAM PEMBELAJARAN DAN PENELITIAN - RESMIA TRIRAHMA; Elieser Tarigan; Wyna Herdiana (CALYPTRA, 2018)
Abstract - Lack of functional effectiveness and convenience of OPAC station facilities that doesn't look neat can reduce the aesthetics and less appealling for the library visitor to visit the library. Therefore it is necessary to redesign the furniture as supporting OPAC station facilities in accordance with the needs of the library of the University of Surabaya. The purpose of this research is to redesign the furniture of OPAC station library of the University of Surabaya as an effort to improve the aesthetics and effectiveness of facility function in learning and research. The method used in this design is qualitative method with Focus Group Discussion and observation in second floor of University of Surabaya's library. From the results of research and design, it is known that the furniture for OPAC station designed with modular and knockdown system will improve the effectiveness of the function of the facility because the product components can be removed to adjust the development of devices that will be used in the future such as computers with built-in CPU or touchscreen device. With a more closed design can make OPAC station more tidy so it can improve the aesthetics of the furniture product itself and the library space.